The body and corporeity in the context of environmental education with an ecological orientation - Strongoli, Raffaella C. (Studi sulla Formazione/Open Journal of Education, 2019)
In this paper, we have taken up the recent line of investigation into eco- pedagogy, refusing reductionist approaches and perspectives that consider the natural environment as a mere element, object or tool that is disconnected from the everyday lives of most people. The aim of the paper is to conduct an analysis of the teaching dimensions regarding environmental education with a wide-ranging ecological perspective. In particular, the text examines the body and corporeity as the basic elements of the experience, knowledge, and development of behaviors oriented in an ecological sense within the teacher-student relationship and the school context.